2020
DOI: 10.1194/jlr.p120000976
|View full text |Cite
|
Sign up to set email alerts
|

Progression of chronic kidney disease in familial LCAT deficiency: a follow-up of the Italian cohort

Abstract: Familial LCAT deficiency (FLD) is a rare genetic disorder of HDL metabolism, caused by loss-of-function mutations in the LCAT gene and characterized by a variety of symptoms including corneal opacities and kidney failure. Renal disease represents the leading cause of morbidity and mortality in FLD cases. However, the prognosis is not known and the rate of deterioration of kidney function is variable and unpredictable from patient-to-patient. In this paper, we present data from a follow-up of the large Italian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Indices of renal function such as serum creatinine and creatinine clearance usually remain normal in the first three decades of life [ 88 ]. Due to the rarity of the disease, the natural history of FLD is still largely unknown; however, a recent work has analyzed the progression of the disease in 18 FLD carriers followed, in some cases, for more than two decades [ 89 ]. In this Italian cohort, half of the FLD patients had the first renal event, classified as kidney failure or kidney transplantation or death for renal complications, by the age of 46 years, with median time to a second event of 10 years [ 89 ].…”
Section: Genetic Hdl Defects and Ckdmentioning
confidence: 99%
See 3 more Smart Citations
“…Indices of renal function such as serum creatinine and creatinine clearance usually remain normal in the first three decades of life [ 88 ]. Due to the rarity of the disease, the natural history of FLD is still largely unknown; however, a recent work has analyzed the progression of the disease in 18 FLD carriers followed, in some cases, for more than two decades [ 89 ]. In this Italian cohort, half of the FLD patients had the first renal event, classified as kidney failure or kidney transplantation or death for renal complications, by the age of 46 years, with median time to a second event of 10 years [ 89 ].…”
Section: Genetic Hdl Defects and Ckdmentioning
confidence: 99%
“…Due to the rarity of the disease, the natural history of FLD is still largely unknown; however, a recent work has analyzed the progression of the disease in 18 FLD carriers followed, in some cases, for more than two decades [ 89 ]. In this Italian cohort, half of the FLD patients had the first renal event, classified as kidney failure or kidney transplantation or death for renal complications, by the age of 46 years, with median time to a second event of 10 years [ 89 ]. Even within the same family, the development and progression of renal damage in FLD patients are highly variable [ 52 , 77 ], suggesting that different genetic and environmental factors can impact on kidney deterioration.…”
Section: Genetic Hdl Defects and Ckdmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction requires the presence of helical apolipoproteins such as apolipoprotein (apo) A-I and E. It takes place on HDL, where particles are initially assembled as disclike particles from extracellular helical apolipoproteins of 3.56 mL/min/1.73 m 2 , whereas deterioration in heterozygous members and family controls was 1.33 and 0.68 mL/min/1.73 m 2 , respectively 36) . A recent Italian cohort study in which 18 FLD patients (12 males and 6 females) were followed up for 12 8.5 years reported that renal events (dialysis, kidney transplant, or death due to renal complications) occur at a median age of 46 years 37) .…”
Section: ) Dyslipidemiamentioning
confidence: 99%